Inborn errors of metabolism associated with psychosis: literature review and case–control study using exome data from 5090 adult individuals. Issue 4 (16th February 2017) - Trakadis, Yannis J.; Fulginiti, Vanessa; Walterfang, Mark
Abstract: A literature review was conducted, using the computerized "Online Mendelian Inheritance in Man" (OMIM) and PubMed, to identify inborn errors of metabolism (IEM) in which psychosis may be a predominant feature or the initial presenting symptom. Different combinations of the following keywords were searched using OMIM: "psychosis", "schizophrenia", or "hallucinations" and "metabolic", "inborn error of metabolism", "inborn errors of metabolism", "biochemical genetics", or "metabolic genetics". The OMIM search generated 126 OMIM entries, 40 of which were well known IEM. After removing IEM lacking evidence in PubMed for an association with psychosis, 29 OMIM entries were identified. Several of these IEM are treatable. They involve different small organelles (lysosomes, peroxisomes, mitochondria), iron or copper accumulation, as well as defects in other met‐abolic pathways (e.g., defects leading to hyperammonemia or homocystinemia). A clinical checklist summarizing the key features of these conditions and a guide to clinical approach are provided. The genes corresponding to each of these con‐ditions were identified. Whole exome data from 2545 adult cases with schizophrenia and 2545 unrelated controls, accessed via the Database of Genotypes and Phenotypes (dbGaP), were analyzed for rare functional variants in these genes. The odds ratio of having a rare functional variant in cases versus controls was calculated for each gene. Eight genes are significantly associated with schizophrenia ( p  < 0.05, OR >1) using an unselected group of adult patients with schizophrenia. Increased awareness of clinical clues for these IEM will optimize referrals and timely metabolic interventions.